123k views
3 votes
Va rog e urgent am nevoie de raspuns

Va rog e urgent am nevoie de raspuns-example-1
User Sherika
by
5.9k points

1 Answer

6 votes

Answer: 4

Step-by-step explanation:

f(x) = 2x - 1

f(√2) = 2√2 - 1

f(1) = 2(1) - 1

= 2 - 1

= 1

f(√3) = 2√3 - 1

*******************************************************


(f(√(2))-f(1))/(√(2)-1) +(f(√(3))-f(√(2)))/(√(3)-√(2))

=
((2√(2)-1)-1)/(√(2)-1) +((2√(3)-1)-(2√(2)-1))/(√(3)-√(2))

=
(2√(2)-2)/(√(2)-1) +(2√(3)-2√(2))/(√(3)-√(2))

=
(2√(2)-2)/(√(2)-1)((√(2)+1)/(√(2)+1))+(2√(3)-2√(2))/(√(3)-√(2))((√(3)+√(2))/(√(3)+√(2)))

=
(4+2√(2)-2√(2)-2)/(2 - 1) + (6 +2√(6)-2√(6)-4)/(3-2)

=
(2)/(1) +(2)/(1)

= 4

User Chris Pearce
by
6.5k points